Changing Tides for the Welfare State - An Essay - Assar Lindbeck (The Research Institute of Industrial Economics (IUI), 2001)
Recent developments in society have generated misalignment between the welfare state and socio-economic conditions and preferences. This paper emphasis developments in the labor market and the structure, stability and preferences of the family, as well as macroeconomic changes. The latter include new patterns of short-term macroeconomic instability, economic growth and the internationalization of national economies. I deal both with developments that are exogenous from the point of view of the welfare state and with developments that may be regarded as endogenous behavior adjustments of individuals in response to the welfare state itself. Alternative welfare-state reforms are also considered.
Keywords: H00; H40; H50; 330; Welfare State; Changes in labor market; Changes in family; Sozialstaat; Arbeitsmarkt; Familie; Bevölkerungsentwicklung; Sozialer Wandel; Strukturwandel; Theorie